Standard Assessments Reveal Context‐Dependent Responses of Crappie Populations to a Length‐Based Regulation in Ohio Reservoirs. (23rd August 2019) - Pritt, Jeremy J.; Conroy, Joseph D.; Page, Kevin S.; Tyszko, Stephen M.; Zweifel, Richard D.
Abstract: Fisheries managers implement minimum length limits (MLLs) to improve the size structure of populations of crappie Pomoxis spp. throughout Midwestern and southeastern U.S. reservoirs. The success of these regulations has been mixed, with several implementations resulting in undesirable outcomes, including slow growth and stunting of crappies, and ultimately regulation removal. Consequently, it is unclear whether and where MLLs should be used to improve crappie size structure. Beginning in 2003, Ohio instituted a statewide standard sampling protocol to monitor reservoir crappie populations, and between 2003 and 2010 a 229‐mm MLL was implemented at over 40 reservoirs throughout the state. Using these spatially and temporally extensive crappie population data, we sought to (1) test for the response of crappie population adult abundance, growth, and size structure to the MLL, (2) test whether reservoir surface area and/or productivity mediated this response, and (3) model fisheries outcomes at different reservoir sizes and productivities to predict where application of a MLL would be most appropriate. Using linear mixed‐effects models and an information theoretic approach, we found that crappie population abundances generally increased, whereas growth decreased in small, unproductive reservoirs but increased in large, productive reservoirs. Overall, the MLL failed to produce increases in size structure, except in large reservoirs. Yield‐per‐recruit models predicted a decrease in angler yield in response to a 229‐mm MLL in small reservoirs, whereas in large, productive reservoirs this regulation was predicted to increase angler yield. Consequently, the MLL could improve crappie fisheries in reservoirs larger than 1, 000 ha with high productivity (total phosphorus concentrations > 50 μg/L) but could be counterproductive in small, unproductive reservoirs. Finally, our approach highlights the benefits of standard sampling as we were able to integrate data across years and reservoirs to make comparisons on a statewide scale.